Attitudes and motivations of competitive cyclists regarding use of banned and legal performance enhancers - Kisaalita, N. R.; Robinson, M. E. (Journal of Sports Science & Medicine, 2014)
Drug `doping` and the use of banned performance enhancing products (PEPs) remains an issue in virtually all competitive sports despite penal consequences and known health risks. The lines distinguishing "fair" and "unfair" performance enhancement have become increasingly blurred. Few studies have explored how attitudes towards legal performance enhancers (drugs/substances, diet, and equipment modifications) may influence motivations to use banned PEPs. In the present study, 68 competitive cyclists completed a survey examining the importance of choosing banned and non-banned PEPs using World Anti-Doping Agency (WADA) and Union Cycliste Internationale (UCI) criteria. Results showed that over 60 percent of cyclists used non-banned PEPs while 8 percent used banned PEPs. Health was overall the most important factor in choosing a PEP while apprehension by a doping agency was least important. Mixed- model ANOVA analyses revealed that motivations to use banned PEPs were complex, as the importance of health, violating the sprit of the sport, performance improvement, and getting caught were differentially influenced by PEP legality (p < 0.001) and whether a cyclist endorsed non-banned PEP use (p < 0.001). The importance of winning, sponsorship, and maintaining competitiveness did not influence non-banned PEP use (p > 0.05). Our findings illustrate the multifactorial nature of PEP use/doping attitudes and highlight the unique role that "legal" performance enhancement may plays in influencing banned and/or unethical sports behaviors.